Pilomatricoma-Study of 3 cases and review of literature - Maharjan, S; Tiwari, M; Ranabhat, S; Shrestha, R (Journal of Chitwan Medical College, 2014)
Pilomatricoma is a benign neoplasm arising from hair follicle matrix cells. It is the most common lesion in pediatric age group. The most frequent sites are head and neck region followed by upper extremities. It is usually asymptomatic and present as a hard, subcutaneous slow-growing mass. Most of the cases present as a single nodule with a size smaller than 3 cm in diameter. We report three cases of pilomatricoma in arm and pre-auricular regions in a child and two young adults. We discuss the clinical presentation and histopathological findings of this uncommon skin tumor, and compare our findings with the previous literature. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10849 Journal of Chitwan Medical College 2014; 4(1): 45-46